'The Finn line' - a historical curiosity or a juridicial rality? The Sami reindeer herders' land rights in southern Sami areas evaluated from land consolidation practice (In Norwegian with Summary in English) - Ravna, Øyvind (Rangifer, 2005)
Attitudes towards the land rights of Sami reindeer herders have changed considerably during the last 100 years. So, too, has consideration of how such rights should be treated by Land Consolidation Courts. This paper reviews changes in attitudes to the Sami land rights with respect to how these are considered in Land Con¬solidation Courts in southern Sami areas in Norway. The review also considers changing attitudes regarding the competence of Land Consolidation Courts to deal with such matters. There were several cases in the 20th Century in which Land Consolidation Courts treated Sami land rights in a restricted and unfortunate manner. Legal practice, however, was not always like that, evidenced by the so-called 'Finn line' (Norwegian: 'finnelinja' -'Finn' is an archaic name for Sami). This boundary was established during a land consolidation case in 1873 and was confirmed in 1883. At that time, Sami land rights were evidently accepted as appurtenant right in privately owned mountain pasture and the Sami were treated in the same way as others who enjoyed rights of usufruct on it. The regulation of 1883 included rules governing compensation for grazing damage on farming land. In particular, responsibility for grazing damage was divided between owners and the reindeer herders, providing these looked after their animals properly, 'The Finn line' subsequently achieved wider importance. The case of 1873¬1883 has been referred to several times as a valuable and valid precedent for a way in which to organize grazing conflicts in other Sami areas. It was used in 1964 as evidence of the special rights of Sami reindeer people in the Brekken common land case. The Sami won this case in 1968 and, in its judgement, the Norwegian Supreme Court of Justice emphasised the importance of the line (Rt. 1968, p. 394). Although, owing to changes in land use practices, the 'Finn line' no longer has any practical significance, its juridical significance remains because it settles the principle that the rights of Sami reindeer herders' have to be considered in the same way as the rights of farming land owners. The ruling of 1873-1883 makes it clear that reindeer herders stand to gain important concessions, with respect to access to pasture, in land consolidation cases. The degradation of Sami land rights from the end of the 19th Century was a consequence of political manipulation and had no basis in law. Attitudes have now changed and, consequently, there is a need to revise recent legislation, such as the 1978 Reindeer Husbandry Act with regard to rules for compensation for grazing damage on farming land, and the 1979 Land Consolidation Act concerning rules of land use.
Keywords: Finn line; history; juridical; Sami land rights; South Sami areas; Sápmi; land consolidation